(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The objectives of our work was to identify the effects of insulin resistance and other hormonal changes on kidney function in newly and previously diagnosed women diseased with PCOS. Method: This prospective study was done by collect serum samples and urine from three group (Control 60), (previously 50), (newly 50) patients. The withdrawal led samples were subsequently assay for hormonal and biochemical changes. Results: The data of tests were available for both groups. We found significant differences in level of insulin, Homeostatic model assessment Insulin resistance (HOMA-IR), Homeostatic model assessment Beta function (HOMA-B), Progesterone among newly and previous women, also the data indicated a significant correlation between urea and testosterone in newly while direct significant correlation between urea and progesterone. There was significant correlation between Thyroid stimulating hormone (TSH) and creatinine in previously diagnosed PCOS, also direct correlation between uric acid and Body mass index (BMI), Fasting blood glucose (FBS), HOMA IR and inverse correlation with Triiodothyronine (T3) in new PCOS while in previously diagnosed PCOS there is inverse correlation between uric acid and T3. Finally, significant correlation between FBS, insulin, HOMA B and HOMA IR in previously diagnosed patients while correlation is seen between FBS, insulin and HOMA IR in newly patients.